Analisis Kemiripan Visual Karakter Wajah Manusia Dalam Perancangan Desain Karakter Wajah 3D “Cerminan Bersaudara” - Putri, Ratih Alifah; Wahyudi, Luqman (Institut Seni Indoensia Surakarta, 2023)
This study proposes an in-depth analysis approach to the visual resemblance of human facial characters within the context of designing 3D facial characters titled